Influence of the Different Dicarboxylate Ligands on The Topological Net of Manganese(II) Coordination Polymers: Syntheses, Crystal Structures. and Luminescent Properties1. Issue 10 (1st June 2015) - Deng, Xiaoqi
Abstract The self‐assembly of MnII ions and 1, 4‐bis(2‐methyl‐imidazole‐1‐yl)benzene (bip) with two different dicarboxylate ligands, benzophenone‐4, 4′‐dicarboxylic acid (H2bda) and 1, 4‐naphthalenedicarboxylic acid (H2nda) via hydrothermal synthesis resulted in two interesting coordination polymers, [Mn(bda)(bip)]n (1) and [(Mn(nda)(bip)0.5(H2O)]n (2). Their structures were determined by single‐crystal X‐ray diffraction and elemental analyses, as well as IR spectroscopy. Complex 1 exhibits an unusual polycatenated 2D+2D→3D framework. Complex 2 shows a twofold interpenetrated pcu net. In addition, the solid‐state photoluminescent properties of 1 and 2 were investigated at room temperature.